A ten-year review of neonatal tetanus cases managed at a tertiary health facility in a resource poor setting: The trend, management challenges and outcome - Ogundare, Ezra Olatunde; Ajite, Adebukola Bidemi; Adeniyi, Adewuyi Temidayo; Babatola, Adefunke Olarinre; Taiwo, Adekunle Bamidele; Fatunla, Odunayo Adebukola; Airemionkhale, Alfred; Odeyemi, Oluwapelumi Adeyosola; Olatunya, Oladele Simeon; Oyelami, Oyeku Akibu (PLOS Neglected Tropical Diseases, 2021)
Background Neonatal Tetanus (NNT) is a vaccine preventable disease of public health importance. It is still being encountered in clinical practice largely in developing countries including Nigeria. NNT results from unhygienic delivery practices and some harmful traditional cord care practices. The easiest, quickest and most cost-effective preventive measure against NNT is vaccination of the pregnant women with the tetanus toxoid (TT) vaccine. The case-fatality rate from tetanus in resource-constrained settings can be close to 100% but can be reduced to 50% if access to basic medical care with adequate number of experienced staff is available. Materials and methods This retrospective study reviewed the admissions into the Special Care Baby Unit (SCBU) of the Ekiti State University Teaching Hospital, Ado-Ekiti from January 2011 to December 2020. The folders were retrieved from the records department of the hospital; Information obtained from folders were entered into a designed proforma for the study. Results During the study period, NNT constituted 0.34% of all neonatal admissions with case fatality rate of 52.6%. Seven [36.8%] of the babies were delivered at Mission home/Traditional Birth Attendant’s place while 5 [26.3%] were delivered in private hospitals. Cord care was with hot water compress in most of these babies16 [48.5%] while only 9% of the mothers cleaned the cord with methylated spirit. Age at presentation of less than one week was significantly associated with mortality, same with presence of autonomic dysfunction. Low family socio-economic class 5 was significantly associated with poor outcome, so also maternal age above 24 years. Conclusion This study revealed that neonatal tetanus is still being seen in our clinical practice with poor outcome and the risk factors are the same as of old. Increased public health campaign, promotion of clean deliveries, safe cord care practices, affordable and accessible health care provision are recommended to combat NNT scourge.